Overlapping Stevens-Johnson Syndrome and DRESS Syndrome Caused by Phenobarbital: A Vietnamese Case Report - Khiem Van Nguyen MD; Quang Van Vu MD, PhD; Mai Hoang Tran MSc; Huy Quoc Nguyen MD, PhD; Chi Quynh Le MD, PhD; Bang Cam Thi Dang MD; Hieu Chi Chu MD; Dinh Van Nguyen MD, PhD (SAGE Publishing, 2023)
Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) Syndrome and Stevens-Johnson Syndrome (SJS) are severe cutaneous adverse reactions to drugs. Those reactions which are rare in children can be especially severe and challenging to diagnose and manage. Herein we present a 59-month-old male who presented with a rash, fever, and multiple organ dysfunction initiation of Phenobarbital for epilepsy. Diagnosis of ovelaping SJS and DRESS syndrome had been made based on clinical manifestations accompanied with skin biopsy according to RegisSCAR diagnostic criteria. A therapy with intravenous immune globulin (IVIG), corticosteroids and supportive care was given successfully for the patient. This case underscored the significance of promptly and effectively recognizing and managing these intricate reactions.